Association of genetic variants in CHEK2 with oesophageal squamous cell carcinoma in the South African Black population. (12th February 2019) - Chen, Wenlong C; Bye, Hannah; Matejcic, Marco; Amar, Ariella; Govender, Dhiren; Khew, Yee Wen; Beynon, Victoria; Kerr, Robyn; Singh, Elvira; Prescott, Natalie J; Lewis, Cathryn M; Babb de Villiers, Chantal; et al.
Abstract: Oesophageal squamous cell carcinoma (OSCC) has a high incidence in southern Africa and a poor prognosis. Limited information is available on the contribution of genetic variants in susceptibility to OSCC in this region. However, recent genome-wide association studies have identified multiple susceptibility loci in Asian and European populations. In this study, we investigated genetic variants from seven OSCC risk loci identified in non-African populations for association with OSCC in the South African Black population. We performed association studies in a total of 1471 cases and 1791 controls from two study sample groups, which included 591 cases and 852 controls from the Western Cape and 880 cases and 939 controls from the Johannesburg region in the Gauteng province. Thereafter, we performed a meta -analysis for 11 variants which had been genotyped in both studies. A single nucleotide polymorphism in the CHEK2 gene, rs1033667, was significantly associated with OSCC [ P = 0.002; odds ratio (OR) = 1.176; 95% confidence interval (CI): 1.06–1.30]. However, single nucleotide polymorphisms in the CASP8 / ALS2CR12, TMEM173, PLCE1, ALDH2, ATP1B2 / TP53 and RUNX1 loci were not associated with the disease ( P > 0.05). The lack of association of six of these loci with OSCC in South African populations may reflect different genetic risk factors in non-African and African populations or differences in the genetic architecture of African genomes. The association at CHEK2, a gene with key roles in cell cycle regulation and DNA repair, in an African population provides further support for the contribution of common genetic variants at this locus to the risk of oesophageal cancer. Abstract : Single nucleotide polymorphisms (SNPs) associated with oesophageal squamous cell carcinoma (OSCC) in Asian populations were genotyped in OSCC cases and controls from the South African Black population. A SNP in CHEK2 was associated with an increased risk of OSCC.